The Effect of the Sport Education Model on Sports Ability: A Critical Systematic Review - Junlong Zhang; Kim Geok Soh; Mohd Ashraff Bin Mohd Anuar; Xiaofei Lin; Lixia Bao; Nasnoor Juzaily Mohd Nasiruddin (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The impact of the Sport Education Model (SEM) and Traditional Teaching (TT) methods on students' sports ability in PE teaching, including game performance, technical performance, and physical fitness is substantial. However, a systematic evaluation of the comparative impact of these two teaching methods on students' sports abilities is lacking. This study aims to assess the difference between Sports Education and traditional teaching methods in enhancing students' sports abilities. Web of Science, PubMed, Scopus, and EBSCOhost (CENTRAL and SPORTDicus) were utilized as databases for a comprehensive search. Eligibility criteria for study selection were developed using the PICOS framework, with the following components: (i) Population - healthy students; (ii) Intervention - any SEM intervention program aimed at improving students' sports ability; (iii) Contrast - any form of traditional teaching methods; (iv) Results - (measured by sports ability, including game performance, technical performance, and physical fitness); and (v) Study design - randomized controlled trial and non-randomized controlled trial. This study analyzed 12 studies, five of which were published in the last five years. Methodological quality was assessed using the Downs and Black checklist, with all studies found to be of moderate quality. The literature’s risk of bias was evaluated using the ROBINS-I tool, and only three articles were at moderate risk of bias, while the rest were at high risk. The results of the majority of studies, which utilized quasi-experimental design with college and junior high school students as participants, indicate that both the Sport Education Model (SEM) and Traditional Teaching (TT) were effective in enhancing students' sports ability. However, SEM demonstrated a superior outcome compared to TT. More than half of the studies failed to meet Siedentop's requirement of a minimum of 18 units. Moreover, the model fidelity in most studies cannot be ensured. Current studies have shown that SEM is more effective than TT in improving students' sports ability. However, these studies lack the universality of objects, and further research is needed to evaluate the effectiveness of SEM on primary and high school students. To ensure reliable results, future studies should prioritize proper planning and design of intervention frequency and quantity. Additionally, model fidelity must be implemented as a necessary procedure.